Generational patterns in home ownership and housing quality among racial/ethnic groups in New York City, 1999 - Friedman, S.; Rosembaum, E.
tbls.
pp. 1492-1533
Keywords: Inmigrantes; Nueva York; Grupos Etnicos y Raciales; Vivienda; Brecha Generacional